Towards the Successful Implementation of Low-Intensity Psychological Interventions: Implementing Problem Management Plus for Venezuelan Migrants and Refugees - PERERA ALADRO, CAMILA (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2020)
Despite available evidence on effective psychological interventions, in low and middle income countries most forcibly displaced persons with mental health problems do not receive any type of mental health care. The last decade has seen growing interest in the use of simple and cost-effective, low-intensity psychological interventions that can be delivered by lay providers. Developed by the World Health Organization, Problem Management Plus (PM+) is a low-intensity psychological intervention for adults suffering from symptoms of common mental health problems (e.g., depression, anxiety, stress or grief), as well as self-identified practical problems (e.g., unemployment, interpersonal conflict). Individual PM+ has been found to be effective in reducing symptoms of psychological distress and PTSD three months post-intervention among non-refugee adult populations, in two randomised control trials conducted in Kenya and Pakistan. Despite these important findings, whether PM+ can be associated with improved psychological outcomes outside of controlled settings is yet to be determined. Similarly, research on the process of adapting these interventions before implementation is needed. Lastly, little is understood about the factors that may contribute or hinder the implementation of these programmes in real-world settings. Methods: These evidence gaps were addressed in three research phases. In phase one, I conducted a systematic review to examine the evidence on low-intensity psychological interventions among forcibly displaced persons, as well as the factors known to influence the implementation of such interventions. The findings of this review informed the subsequent parts of this study and lead to phase two, the cultural adaptation of the intervention under study (i.e. PM+). Phase two sought to determine what contextual and cultural adaptations needed to be made to the PM+ manuals to make the them relevant and meaningful to the implementation context. Within this phase, I developed and applied a four-step process (i.e. information gathering, adaptation hypotheses, local consultation and external evaluations) to culturally adapt PM+. Lastly, the outcomes of the phase two were used in the implementation of PM+ for Venezuelan migrants and refugees living in Saravena, Colombia. Accordingly, phase three of this study involved of the evaluation of the implementation of PM+ through an operational phased-in quasi-experimental study to ascertain the association of PM+ with improved outcomes in subjective wellbeing (the WHO-5 Wellbeing Index), anxiety (Generalised Anxiety Disorder 7) and quality of life (World Health Organization Quality of Life BREF) among the study population. Semi-structured interviews and focus group discussions with intervention participants, PM+ supervisors and lay providers were used to explore the factors influencing the implementation of PM+ in this setting. Results: In phase one, 3,847 relevant references screened, 18 met the inclusion criteria, 15 of which aimed to address child and/or adolescent mental health. Despite the available evidence supporting the use of high and low-intensity versions of CBT interventions, the evidence on low-intensity CBT interventions for forcibly displaced persons identified through this review was scarce and inconclusive. Evidence on the effectiveness and acceptability of parenting skills interventions, narrative exposure therapy, interpersonal psychotherapy and problem-solving counselling was identified. Cultural and contextual adaptations contributed to increasing interventions' relevance and participant retention. Distrust among participants of group interventions, lack of reliable protection of participants and the negative impact of interventions on lay providers' mental health may hinder implementation. Time, resource constraints and weak coordination can also affect the sustainability of these interventions. In phase two, the information gathering step yielded key information on the socioeconomic aspects of the study population, the availability and need for mental health and psychosocial support, and existing barriers to accessing care. The adaptation hypotheses step further identified the need for clearer explanations of key concepts, the need for sensitive topics to match local attitudes (e.g., domestic violence, thoughts of suicide), and the identification of culturally appropriate social supports. Building on these first two steps, local consultation subsequently resulted in revised PM+ protocols. The adapted protocols differed from the original format in their focus on the problems unique to these population groups, the way that psychological distress is expressed in this context, and the inclusion of locally available supports. The results of the external evaluation supported the adaptations made to the PM+ manuals. In phase three, a univariate ANCOVA of the PM+ group's (n=38) post-intervention scores and the control groups' scores at waitlist (n=25), controlling for baseline scores, and demographic variables (i.e. sex, age, level of education), indicated significant effect for the PM+ group across all outcome measures: WHO-5 (n2 = .75, p = <.001); GAD-7 (n2 = .92, p = <.001), WHOQOL-BREF Physical (n2 = .6, p = <.001); WHOQOL-BREF Psychological (n2 = .78, p = <.001); WHOQOL-BREF Social Relationships (n2 = .64, p = <.001); WHOQOL-BREF Environment (n2 = .48, p = <.001). In addition to baseline scores, sex had a significant effect on the WHO-5 scores (n2 = .06, p = .05). Cohen's d and Hedge's g were above 2.5 across all study outcomes. The following factors influenced the implementation of PM+ in this setting: trust, engagement, integrated approach, teamwork, autonomy, supervision, acceptability and inclusion. Conclusions: The results of this study support the use of PM+ as an acceptable approach for decreasing psychological distress among forcibly displaced persons. Although the findings of this study support the implementation of PM+, various factors should be considered and put in place before implementing it. This study contributed to existing knowledge in this topic through a review and analysis of the available evidence on this topic, a new process for culturally adapting low-intensity psychological interventions and a better understanding of the implementation of PM+ by lay providers. The implications of these finding for theory, policy and practice are discussed.
APPROVED
Keywords: Mental health; Low-intensity psychological interventions; Task-sharing; Humanitarian settings; Refugee; Migrant; Cultural adaptation